Saliva stress biomarkers in ERCP trainees before and after familiarisation with ERCP on a virtual simulator - Georgiou, Konstantinos; Boyanov, Nikola; Thanasas, Dimitrios; Sandblom, Gabriel; Linardoutsos, Dimitrios; Enochsson, Lars (Frontiers in Surgery, 2024)
Stress during the early ERCP learning curve may interfere with acquisiHon of skills during training. The purpose of this study was to compare stress biomarkers in the saliva of trainees before and a`er familiarisaHon with ERCP exercises on a virtual simulator.Altogether 26 endoscopists under training, 14 women and 12 men, completed the three phases of this study: Phase 1. Three different ERCP procedures were performed on the simulator. Saliva for α-amylase (sAA), Chromogranin A (sCgA), and CorHsol (sC) were collected before (baseline), halfway through the exercise (ex.), and 10 min a`er compleHon of the exercise (comp.); Phase 2. A three-week familiarisaHon period where at least 30 different cases were performed on the virtual ERCP simulator; and Phase 3. IdenHcal to Phase 1 where saliva samples were once again collected at baseline, during, and a`er the exercise. Percentage differences in biomarker levels between baseline and exercise (Diffex) and between baseline and compleHon (Diffcomp) during Phase 1 and Phase 3 were calculated for each stress marker.Mean % changes, Diffex and Diffcomp, were significantly posiHve (p<0.05) for all markers in both Phase 1 and Phase 3. Diffex in Phase 1 was significantly greater than Diffex in Phase 3 (p<0.05) for sAA and sCgA. Diffcomp for sAA in Phase 1 was significantly greater than Diffcomp in Phase 3 (p<0.05). No significant differences were found in sC concentraHon between Phases 1 and 3.This study shows that familiarisation with the ERCP simulator greatly reduced stress as measured by the three saliva stress biomarkers used with sAA being the best. It also suggests that familiarisation with an ERCP simulator might reduce stress in the clinical setting.